2019
DOI: 10.1021/acs.bioconjchem.8b00674
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Nucleic Acid-Functionalized Adenoviral Vectors Targeting G-Quadruplexes in the P1 Promoter of Bcl-2 Proto-Oncogene: A New Tool for Gene Modulation in Anticancer Therapy

Abstract: The B-cell lymphoma 2 (Bcl-2) gene encodes for an antiapoptotic protein associated with the onset of many human tumors. Several oligonucleotides (ONs) and ON analogues are under study as potential tools to counteract the Bcl-2 expression. Among these are Peptide Nucleic Acids (PNAs). The absence of charges on PNA backbones allows the formation of PNA/DNA complexes provided with higher stability than the corresponding natural DNA/DNA counterparts. To date, the use of PNAs in antigene or antisense strategies is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…CD profile of both the DNA-FAM/PNA and DNA/PNA complexes (Figure 2, blue and green line, respectively) showed the typical spectrum of antiparallel heteroduplexes characterized by two CD maxima around 260 nm and 220 nm and two minima around 240 nm and 200 nm, thus confirming the formation of the heteroduplexes [3,5,6,45]. Moreover, a slight reduction of the positive dichroic signals at 269 nm observed for the DNA-FAM/PNA in comparison with DNA/PNA profile could be ascribed to the presence of the FAM chromophore.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…CD profile of both the DNA-FAM/PNA and DNA/PNA complexes (Figure 2, blue and green line, respectively) showed the typical spectrum of antiparallel heteroduplexes characterized by two CD maxima around 260 nm and 220 nm and two minima around 240 nm and 200 nm, thus confirming the formation of the heteroduplexes [3,5,6,45]. Moreover, a slight reduction of the positive dichroic signals at 269 nm observed for the DNA-FAM/PNA in comparison with DNA/PNA profile could be ascribed to the presence of the FAM chromophore.…”
Section: Resultsmentioning
confidence: 65%
“…PNA sequence ( Table 1) was synthesized using the 9-fluorenylmethoxycarbonyl (Fmoc) solidphase strategy, following the protocol reported elsewhere [6]. The raw product was purified by semipreparative HPLC analyses by Jasco (Easton, MD, USA) Plus pump equipped with a Jasco UV-2075 Plus UV detector using a 10 × 250 mm C-18 reverse-phase column (particle size 5 µm)(Merck Millipore Billerica, MA, USA) eluted with a linear gradient of CH3CN containing 0.1% (v/v) trifluoroacetic acid (TFA) in H2O containing 0.1% (v/v) TFA (from 0 to 100% in 45 min, flow 1.2 mL/min).…”
Section: Pna Synthesis Purification and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, linear α,ε-PLLs, easily obtainable by standard solidphase peptide synthesis procedures [15,18,19] and endowed with structural specific nucleic acids binding abilities, do not show any significant degradation after 24 h of incubation in human serum at 37 °C [14]. Among the DNA secondary structures, the G-quadruplex (G4) family is one of the most intriguing and deeply investigated [20][21][22][23]. It has been demonstrated that G4 DNA plays a crucial role in many physiological and disease-related biological mechanisms [24].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the ubiquitous potassium or sodium cations, positively-charged polyamines and triethylene tetraamine may contribute to the G4 stability and induce biologically-relevant effects [25,26]. In this context, also the polycationic PLL was evaluated for its impact on the formation of G4 structures by the human telomere in cation-deficient media and showed the interesting ability to convert the telomeric G4 Among the DNA secondary structures, the G-quadruplex (G4) family is one of the most intriguing and deeply investigated [20][21][22][23]. It has been demonstrated that G4 DNA plays a crucial role in many physiological and disease-related biological mechanisms [24].…”
Section: Introductionmentioning
confidence: 99%